The Link Between Ferroptosis and Cardiovascular Diseases: A Novel Target for Treatment - Huilin Hu; Yunqing Chen; Lele Jing; Changlin Zhai; Liang Shen (Frontiers in Cardiovascular Medicine, 2021)
Ferroptosis is an iron-dependent cell death, which is characterized by iron overload and lipid peroxidation. Ferroptosis is distinct from apoptosis, necroptosis, autophagy, and other types of cell death in morphology and function. Ferroptosis is regulated by a variety of factors and controlled by several mechanisms, including mitochondrial activity and metabolism of iron, lipid, and amino acids. Accumulating evidence shows that ferroptosis is closely related to a majority of cardiovascular diseases (CVDs), including cardiomyopathy, myocardial infarction, ischemia/reperfusion injury, heart failure, and atherosclerosis. This review summarizes the current status of ferroptosis and discusses ferroptosis as a potential therapeutic target for CVDs.